ANALISISPENGGUNAAN METODE QUANTITATIVE STRATEGIC PLANNING MATRIX (QSPM) UNTUK MERUMUSKAN STRATEGI PEMASARAN PADA CAFÉ COKLAT KLASIK MALANG - Nurul Hidayah; Muhammad Hufron; Afi Rachmat Slamet (E-JRM : Elektronik Jurnal Riset Manajemen, 2017)
ABSTRACTThe purpose of this research is to get alternative strategy from result ofinternal factor analysis and external factor so get alternative of formula ofmarketing strategy that appropriately and can be applied for Classic ChocolateCafé Malang. Based on the results of research formulation of QuantitativeStrategic Planning Matrix (QSPM) method, the alternative strategy is to improvethe management and cooperation capability for the company purpose, Improvingthe service quality to attract the consumers. Maintain an economical price andimprove product quality to increase consumer loyalty. Utilize a strategic locationand satisfactory facilities to add potential customers. The alternative strategy ismore prioritized because, for this strategy company can take advantage ofinternal strength in order to benefit from existing external opportunities. The mainpriority result of the analysis is the SO strategy with TAS (Total AttractivenessScore) of 6.716.Keywords: Marketing Strategy, IFE Matrix, EFE, IE, SWOT, QSPM.